2007
DOI: 10.1007/s00253-006-0820-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and identification of novel cellulase genes from uncultured microorganisms in rabbit cecum and characterization of the expressed cellulases

Abstract: A metagenomic cosmid library was prepared in Escherichia coli from DNA extracted from the contents of rabbit cecum and screened for cellulase activities. Eleven independent clones expressing cellulase activities (four endo-beta-1,4-glucanases and seven beta-glucosidases) were isolated. Subcloning and sequencing analysis of these clones identified 11 cellulase genes; the encoded products of which shared less than 50% identities and 70% similarities to cellulases in the databases. All four endo-beta-1,4-glucanas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
88
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 33 publications
5
88
1
5
Order By: Relevance
“…Zheng et al (66) reported three main hypotheses explaining the enhancement of enzymatic cellulose hydrolysis in the presence of nonionic surfactants: (i) they stabilize the enzyme by reducing thermal and/or mechanical shear forces; (ii) they change the substrate structure, enhancing substrate accessibility; and (iii) they affect enzymesubstrate interaction, preventing enzyme inactivation due to nonproductive adsorption when, for example, lignocellulosic substrates are being hydrolyzed. This last hypothesis does not concern the substrate we used (CMC), and as, generally, no significant (positive or negative) effect of Triton X-100 has been observed on other bacterial cellulase activities characterized with CMC (9,54,63,67), the second hypothesis must not be the reason why Cell5.1_3 activity increases to 350% in the presence of Triton X-100. However, Cell5.1_3 is probably more stable, and therefore more active on CMC, in the presence of Triton X-100.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al (66) reported three main hypotheses explaining the enhancement of enzymatic cellulose hydrolysis in the presence of nonionic surfactants: (i) they stabilize the enzyme by reducing thermal and/or mechanical shear forces; (ii) they change the substrate structure, enhancing substrate accessibility; and (iii) they affect enzymesubstrate interaction, preventing enzyme inactivation due to nonproductive adsorption when, for example, lignocellulosic substrates are being hydrolyzed. This last hypothesis does not concern the substrate we used (CMC), and as, generally, no significant (positive or negative) effect of Triton X-100 has been observed on other bacterial cellulase activities characterized with CMC (9,54,63,67), the second hypothesis must not be the reason why Cell5.1_3 activity increases to 350% in the presence of Triton X-100. However, Cell5.1_3 is probably more stable, and therefore more active on CMC, in the presence of Triton X-100.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, several groups isolated novel enzymes from various environments (Ranjan et al, 2005;Rhee et al, 2005;Feng et al, 2007;Hardeman and Sjoling, 2007;Tirawongsaroj et al, 2008), and many of them were found to offer a good potential as new tools for industrial applications, because their biophysical properties arise from improved adaptations to the conditions met in the environment during the sampling process. Although such studies reported the characterization of metagenome-derived enzymes, insights into their physiological aspect are often lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This can be addressed by functional screening of metagenomic libraries, in order to retrieve genes of interest. Numerous studies have provided conclusive evidence on the potential of such an approach for the identification of novel glycoside-hydrolases from various ecosystems such as soil (Rondon et al 2000;Richardson et al 2002;Voget et al 2003;Pang et al 2009), lakes (Rees et al 2003), hot springs (Tang et al 2006, rumen (Ferrer et al 2005;Guo et al 2008;Liu et al 2008;Duan et al 2009), rabbit (Feng et al 2007), and insect guts (Brennan et al 2004; for review, see Ferrer et al 2009;Li et al 2009;Simon and Daniel 2009;Uchiyama and Miyazaki 2009). In all cases, the identification of the gene responsible for the screened activity was carried out by sequencing only a few kilobases of metagenomic DNA.…”
mentioning
confidence: 99%